Mitochondrial Deficits With Neural and Social Damage in Early-Stage Alzheimer’s Disease Model Mice - Misrani, Afzal; Tabassum, Sidra; Huo, Qingwei; Tabassum, Sumaiya; Jiang, Jinxiang; Ahmed, Adeel; Chen, Xiangmao; Zhou, Jianwen; Zhang, Jiajia; Liu, Sha; Feng, Xiaoyi; Long, Cheng; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer's disease (AD) is the most common neurodegenerative disorder worldwide. Mitochondrial dysfunction is thought to be an early event in the onset and progression of AD; however, the precise underlying mechanisms remain unclear. In this study, we investigated mitochondrial proteins involved in organelle dynamics and energy production in the medial prefrontal cortex (mPFC) and hippocampus (HIPP) of young (1~2 months), adult (4~5 months) and aged (9~10, 12~18 months) APP/PS1 mice. We observed increased levels of mitochondrial fission protein, Drp1, and decreased levels of ATP synthase subunit, ATP5A, leading to increased oxidative stress, glial activation, apoptosis, and altered neuronal morphology as early as 4~5 months of age in APP/PS1 mice. Electrophysiological recordings revealed abnormal miniature excitatory postsynaptic current in the mPFC together with a minor connectivity change between the mPFC and HIPP, correlating with social deficits. These results suggest that abnormal mitochondrial dynamics, which worsen with disease progression, could be a biomarker of early-stage AD. Therapeutic interventions that improve mitochondrial function thus represent a promising approach for slowing the progression or delaying the onset of AD.